Smaller countries' way to competitiveness: Central America in a New World Economic Order during the 90s - Bermudez, Gerardo Zepeda ([s. n.] [S. l.], 1992)
Looks at aspects such as Central America today and the aftermath of import substitution strategies; small and medium-scaled enterprises in Central American industrialization; and Central America's new goal : an economic community.